Analysis of modern tools, methods of audit and monitoring of database security - Mykhailyshyn, Kateryna; Harasymchuk, Oleh; Deineka, Oleh; Dreis, Yurii; Shulha, Volodymyr; Pepa, Yuriy (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2025)
The mismatch between modern technological innovations and traditional approaches to information security can significantly affect the effectiveness of database monitoring systems. This paper examines the ethical and legal aspects of database monitoring, taking into account current regulatory requirements and the importance of maintaining data confidentiality. The study also evaluates the use of each tool to determine their effectiveness in real-world conditions, the possibility of improving the functional characteristics of monitoring systems, their adaptation to new technologies and increasing the overall level of information protection.